2016
DOI: 10.1016/j.jsv.2016.01.051
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency vibration energy harvesting from impulsive excitation utilizing intentional dynamic instability caused by strong nonlinearity

Abstract: The authors investigate a vibration-based energy harvesting system utilizing essential (nonlinearizable) nonlinearities and electromagnetic coupling elements. The system consists of a grounded, weakly damped linear oscillator (primary system) subjected to a single impulsive load. This primary system is coupled to a lightweight, damped oscillating attachment (denoted as nonlinear energy sink, NES) via a neodymium magnet and an inductance coil, and a piano wire, which generates an essential geometric cubic stiff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 32 publications
(103 reference statements)
4
33
0
Order By: Relevance
“…The PEH is regarded as an AC voltage in series with a capacitor [77]. Based on Equations (5) and (6), the system model is given in Equations (10) and (11).…”
Section: Impedance Matching For the Pehmentioning
confidence: 99%
See 2 more Smart Citations
“…The PEH is regarded as an AC voltage in series with a capacitor [77]. Based on Equations (5) and (6), the system model is given in Equations (10) and (11).…”
Section: Impedance Matching For the Pehmentioning
confidence: 99%
“…where k ij represents the piezoelectric coupling coefficient, V R the voltage across load resistance, C the capacitance of PEH, R the load resistance, I the moment of inertia of beam, t the thickness of piezoelectric material and y the displacement of input vibrations. When the external excitation frequency is equal to the resonant frequency of PEH, the output power can be analyzed from Equations (10) and (11) as given in Equation 14.…”
Section: Impedance Matching For the Pehmentioning
confidence: 99%
See 1 more Smart Citation
“…Inertial harvesting mechanisms are commonly used in energy harvesters for industrial applications where numerous linear and nonlinear structures have been demonstrated [14], [15]. In the environment of the human body, however, this approach bears considerable additional challenges.…”
Section: Introductionmentioning
confidence: 99%
“…However, many devices (most notably sensors in hazardous environments) contain energy harvesting technologies. Solar cells are probably the most common example, but some sensors also harvest energy from ambient vibrations [8,9] or electromagnetic radiation [10] (e.g., from communication technologies such as television transmitters). To get a rough feeling for the involved scales (see also [10]), note that batteries can store on the order of a joule of energy per cubic millimeter, while solar cells provide several hundred microwatt per square millimeter in bright sunlight, and both vibrations and ambient radiation technologies provide on the order of nanowatt per cubic millimeter.…”
Section: Introductionmentioning
confidence: 99%